Micro-scale contact behavior and its effect on the material removal process during chemical mechanical polishing. (April 2021) - Wang, Lin; Zhou, Ping; Yan, Ying; Hou, Changyu; Guo, Dongming
Abstract: A real-time coefficient of friction (COF) analysis method, in conjunction with an in-situ contact area measurement method, is used to determine the frictional and material removal behaviors induced by the micro-scale pad asperity. The results indicate that the material removal rate (MRR) shows no correlation with the average COF, but shows a strong relationship with the fluctuation of the friction force, i.e. the stick-slip phenomenon. Moreover, a waviness topography is observed on the polished surface, which is further verified to be raised from the stick-slip phenomenon. Futhermore, a micro-asperity scale model is established to explain the underlying mechanism of stick-slip phenomenon. The results provide some new insights into the material removal mechanisms and the real-time monitoring technology for the CMP process. Graphical abstract: Image 1 Highlights: Effects of micro-scale contact behavior on MRR are evaluated. Fluctuation of COF has a significant effect on the MRR. Waviness topography is produced by the unstable tribochemical wear process. The stick-slip vibration of microscale contact is analyzed mathematically.